2015
DOI: 10.5897/ajb2015.14535
|View full text |Cite
|
Sign up to set email alerts
|

Grain yield and its components study and their association with normalized difference vegetation index (NDVI) under terminal water deficit and well-irrigated conditions in wheat (Triticum durum Desf. and Triticum aestivum L.)

Abstract: Six genotype of Triticum aestivum L. in 1991 and one genotype of Triticum durum Desf. and three of T. aestivum L. in 1992 were studied under different water regimes: full irrigation (R1), mild water stress (R3) and severe water stress (R2) at Magneraud (France). Traits evaluated were grain yield and its components, stress susceptibility index (SSI) and normalized difference vegetation index (NDVI). The analysis of variance revealed significant differences between regimes and among the cultivars for all traits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(16 reference statements)
2
3
0
Order By: Relevance
“…Bread wheat genotypes were superior to durum wheat genotypes for their yield and tolerance to drought stress. Our result is in agreement with result of Mekliche et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…Bread wheat genotypes were superior to durum wheat genotypes for their yield and tolerance to drought stress. Our result is in agreement with result of Mekliche et al (2015).…”
Section: Discussionsupporting
confidence: 83%
“…These results show that NDVI can use to estimate the grain yield. Similar results were reported by Roy et al (2021), Marti et al (2007), Sultana et al (2014), Morgounov et al (2014), Mekliche et al (2015).…”
Section: Normalized Difference Vegetation Indexsupporting
confidence: 91%
“…Since the NDVI is an indirect measurement of biomass, this positive regression can be associated with plant density per unit area which is one of the yield components. Mekliche et al (2015) suggested that the grain yield could be predicted using a single regression with NDVI. In addition to grain yield, Hazratkulova et al (2012) also stated that NDVI can be used for identifying physiological superior.…”
Section: Normalized Difference Vegetation Indexmentioning
confidence: 99%
“…Studies regarding the effect of CA practices and several nitrogen fertilization levels on chlorophyll content and nitrogen status of durum wheat in relation to vegetation indices are lacking. For example, some studies showed that the yield estimated from the normalized difference vegetation index (NDVI) had a strong relationship with grain yield in wheat [35,36] in addition, NDVI has also been used to estimate crop growth status based on the different patterns of reflection of green organs and soil in wheat and other cereals [37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%